Crop rotation. VII. Effects of winter crops on yield and on some agronomic characteristics of soybean plants from 1979 to 1985 - Santos, Henrique Pereira dos; Pereira, Luiz Ricardo (Pesquisa Agropecuaria Brasileira, 2014)
During a six-year period at EMBRAPA/Centro Nacional de Pesquisa de Trigo (CNPT) at Passo Fundo, RS, Brazil, the productivity and some agronomic characteristics of soybean plants in succession to winter crops were assessed. Soybeans were direct seeded on oats, rapeseed, flax, lupine and wheat stubble. The winter crops followed a rotational schedule and were arranged in a complete randomized block design and replicated four times. Both sowing and harvesting were mechanically done in plots with 120 m2. The means for soybean yield, plant height and insertion of the first pods were not affected by winter crops, nevertheless, yield components such as number of legumes, and number of grains were influenced by the preceeding winter crops. Soybeans seeded after wheat showed the highest yield.
Keywords: succession; oats; rapeseed; flax; lupine; wheat; direct drilling